Effect of Particle Porosity on Hysteresis in Trickle-Bed Reactors - Maiti, Rabindranath; Atta, Arnab; Nigam, K. D. P (Industrial & engineering chemistry research, 2008)
Hydrodynamics in trickle-bed reactors (TBRs) is quite complex because of the coexistence of gas−liquid−solid phases. Recent past hysteresis have been the subject of investigation to improve the understanding of the flow features at the microlevel, aiming to demystify the complex hydrodynamics. The purpose of the present study is to identify the role of particle porosity on hysteresis by choosing particles of different pore density (nonporous, semiporous, porous) but prepared from same material with identical shape and sizes. Experiments were carried out with industrial relevant-sized alumina extrudates in a 150 mm ID column using both a dry- and a wet-bed startup procedure. Comprehensive pressure drop hysteresis data were generated in increasing and decreasing modes of water flow in the presence of a constant flow of air at ambient condition. Pronounced but different magnitudes of pressure drop hysteresis were observed with all three types of particles at first cycle as well at subsequent cycle of operation. A deviation in pressure drop up to 90% was found between increasing and decreasing modes of operation, even after prewetting the bed. The same amount of hysteresis was observed for all the subsequent cycles, but the value is higher for particles with higher porosity. This confirms that particle porosity plays a major role in the existence of different flow texture at the microlevel in the trickle flow regime. This observation is reported here for the first time, and we believe that there is no such experimental data available in the literature. The genesis of this different hysteretic behavior of porous particles lies in the different ways liquid spreads/retracts over porous and nonporous particles. A conceptual framework of hysteresis proposed by Maiti et al. (2005), which is based on the concept of participating and nonparticipating particles and principles of liquid spreading on porous and nonporous substrates, is found to explain successfully the various features of hysteresis observed with all three types of particles. This study is expected to be useful to the TBR researcher and practitioner in enhancing the understanding further to demystify the complex hydrodynamic phenomena in TBRs.